IDENTIFIKASI DAERAH RAWAN LONGSOR DAN PENANGGULANGANNYA DI KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Rahmah Rahmah; Sulistyarini Sulistyarini; Ludovicus Manditya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine the spatial distribution of landslide vulnerability and its mitigation in Sungai Pinyuh District Mempawah District. This type of research is qualitative. Data collection methods are observation and documentation. The data analysis technique used is descriptive analysis, using GIS (Geographic Information System) 10.1 application with weighted tiered quantitative overlay modeling. The results of this study indicate that: 1) The level of landslide susceptibility in Sungai Pinyuh District consists of 3 classes: low (not prone), moderate (prone) and high (very vulnerable). (a) Areas that are not vulnerable are spread throughout the villages in Sungai Pinyuh District. (b) Areas with moderate level of vulnerability (vulnerable) are spread in Galang Village (0.24%), Nusapati Village (1.74%), Peniraman Village (3.22%), Sungai Pinyuh Village (1.18%), and Sungai Purun Kecil Village (0.11%). (c) Areas with a high level of vulnerability (very vulnerable) are only found in Peniraman Village, which has 223 ha or 1.15% of the total area of Sungai Pinyuh District. 2) the location of the observation points shows that there are seven points selected, including six points with a level of vulnerability and one point with a very vulnerable level, then of the seven have different land use characteristicsKeywords : Landslide Areas, Landslide Management